(untitled) (Conferencea, 2023)
Russian poetry has always been an integral part of national culture and history. Through poetry, we can see that love is the greatest source of inspiration for Russian poets and that women have a special place in this art. Individually, Russian poets revealed their feelings, experiences and love for women, created masterpieces of world literature.